The Establishment of Animation Video Media at Vocational Sschool Lesson Grade V SDN 14 Koto Baru, Dharmasraya - Yulia Darniyanti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
This research is based on the rill problems, the lack of teaching media that attracts the attention of class V in social lessons, that can make the students do not interest in participating learning process. The efforts to fix these problems are by using teaching media that are able to make students interested and participating in the teaching and learning process, namely animation video media. The type of this research is research and development by using a 4-D model consisting on define, design, development, and disseminate stages. The results of the validation of the social lesson content animation video media on the validity test by three experts, that have an average score of 90% which is included in the valid category, the practicality test with an average score of 95% which is categorized as practical, while the results of the effectiveness of the video with animation have an average score 83% on average effective. Based on the results of the analysis above, it can be said that the animation video for teaching media in social lesson for class V SD makes easier for students to understand the learning material